Experimental Study on Bio-cementation of Red Mud Through Microbially Induced Calcite Precipitation - Dhriyan S.S.; Prasad A.; Verma A.K. (My University, 2025)
Red mud, a byproduct of aluminium production, has significant environmental implications, requiring extensive land, substantial earth material, and considerable expenditure for disposal. Its high alkalinity and toxicity threaten air, land, and water resources. Proper management of red mud is crucial for environmental protection. This study employed bio-cementation technique known as the microbial-induced calcite precipitation (MICP) to stabilize red mud. The urease enzyme-producing bacterial strains, Bacillus sphaericus (BS) and Bacillus megaterium (BM), were utilized for treatment. This study assessed MICP impact on red mud by examining variations in calcite content, pH, unconfined compressive strength (UCS), and stress–strain characteristics. The results demonstrated the effectiveness of MICP in treating red mud. The study also investigated the influence of environmental temperature and cementing solution molarity on calcite production and subsequent strength gain. Bio-cemented red mud by BS and BM exhibited UCS values as high as 958 kPa and 814 kPa, respectively, compared to 208 kPa for untreated red mud. Calcite precipitation by bacteria was highest at 40 °C and one molar concentration of the cementing solution. MICP enhanced shear strength parameters while neutralizing red mud’s alkalinity. Microbial treatment transformed the morphology of red mud, showcasing potential applications in embankments, foundations, and structural fills on a large scale. © The Author(s), under exclusive licence to Indian Geotechnical Society 2024.